Manipulações alimentares em diferentes fases do desenvolvimento de bovinos - Costa, Natália Alves (2019)
The objective of this study was to evaluate the physiological, biochemical and metabolic effects of milk restriction and prebiotic supplementation in suckling calves, and the same effects of supplementation of taurine in the bovine termination phase. Two experiments were executed to achieve the mentioned objectives. In the first trial it was used 20 crossbred calves with approximate initial weight of 38 kg and housed in individual pens for 56 days divided into two periods of 28 days each. The animals were allocaded in four experimental groups: animals receiving 6 L of milk in periods 1 and 2 (CON), animals with 50% milk restriction in the first period and re-alimented in the second period (RES), animals without restriction and supplemented of 5 g/day of mannanoligosaccharide (MOS) or mannan- frutoligosaccharide (MFOS). The weight gain and feed intake were verified. Serum was used to determinate glucose, lactate, creatinine, alkaline phosphatase, triglycerides, urea, toal protein and the hormones ghrelin and leptin. In the brain, in the paraventricular region of the hypothalamus, ghrelin receptor expression (GHS-R1a) was evaluated. The rumen and small intestine were used to evaluate the development of the gastrointestinal tract: rumen papilla length, villus height and intestinal crypt depth. We observed a lower weight gain of the restricted group in the first period and no difference in the weight gain among groups in the second period. It was observed that animals from the prebiotic supplemented (MOS) group showed a significant increase in jejunal villus height. Ruminal development was favored by the supplementation of mannanoligosaccharides (MOS group), which significantly increased ruminal papillae length. No difference was found for serum concentration of ghrelin and leptin among treatments in periods 1 and 2 (P> 0.05). Regarding the expression of ghrelin receptors in the paraventricular region of the hypothalamus, there was no difference between the groups evaluated. The second experiment was performed in 123 days with 80 finishing steers, mean initial weight of 507 kg and divided into groups supplemented with: 0; 0.025; 0.05; 0.075 and 0.1% taurine in the diet. Changes in performance were evaluated by weighing and control of the daily feed intake, carcass traits were evaluated after animals slaughter with data provided by the slaughter hose, and the metabolic changes were measured by plasma glucose, lactate, taurine and triglycerides values. Immediately after slaughter, a sample of Sternocephalicus ventrally muscle was collected to analyze the glycolytic potential. To complement the data from the second in vivo assay, an in vitro assay was performed using ruminal fluid cultures. Measurements included concentrations of VFA, pH, IVDMD and fermentative gas production for cultures containing 0; 0.025; 0.05; 0.075 and 0.1% taurine on the substrate. Supplementation of taurine did not affect the final characteristics of weight, HCW, DMI and carcass traits. Blood metabolites were not affected by administration of taurine. In addition, the production of in vitro gases, the concentrations of IVDMD and VFA’s were not affected by the addition of taurine. A linear response was detected for pH (P = 0.006) and with cattle consuming 0.1% taurine had the lowest pH. The compensatory gain presented by the restrictd milk animals, but did not accelerate the intestinal and ruminal development, while the supplementation of mananoligosaccharides caused an accelerated growth of the ruminal papillae and villi of the jejunum. Mannan-frutoligosaccharide supplementation did not accelerate the development of suckling calves. Taurine supplementation did not cause any change in the finishing phase of cattle, however, it caused a decrease in rumen pH.